Non-stoichiometric molybdenum sulfide clusters and their reactions with the hydrogen molecule. Issue 1 (21st December 2020) - Chen, Yan; Deng, Jia-Jun; Yao, Wen-Wen; Gurti, Joseph Israel; Li, Wei; Wang, Wen-Jie; Yao, Jian-Xi; Ding, Xun-Lei
Abstract : The empty bridge  site of Mo–Mo in non-stoichiometric molybdenum sulfide clusters may act a bridge for H atom transfer and be beneficial for hydrogen evolution reaction. Abstract : Structures of non-stoichiometric Mo x S y clusters ( x = 2–4; y = 2–10) were studied by density functional calculations with global optimization. Besides 1T phase like structures, a novel regular grid structure in which Mo atoms are well separated by S atoms was found, which might be used as a building-block to construct a new type of two-dimensional molybdenum sulfide monolayer. The hydrogen molecule prefers to be adsorbed onto Mo atoms rather than S atoms, and Mo atoms with less S coordination have a higher ability to adsorb H2 . In addition, the reaction pathways for H2 dissociation were studied on two clusters with the highest H2 adsorption energy (Mo2 S4 and Mo3 S3 ). The vacant bridge site of Mo–Mo in S-deficient clusters, which corresponds to the sulfur vacancy in the bulk phase MoS2, is favored by H atom adsorption and plays an important role in the H atom transfer on Mo x S y clusters. Our results provide a new aspect to understand the reason why S defect in MoS2 and MoS2 with an Mo-edge could enhance the catalytic performance in the hydrogen evolution reaction.